2015
DOI: 10.1002/2015jb011870
|View full text |Cite
|
Sign up to set email alerts
|

Body wave extraction and tomography at Long Beach, California, with ambient‐noise interferometry

Abstract: We retrieve P diving waves by applying seismic interferometry to ambient‐noise records observed at Long Beach, California, and invert travel times of these waves to estimate 3‐D P wave velocity structure. The ambient noise is recorded by a 2‐D dense and large network, which has about 2500 receivers with 100 m spacing. Compared to surface wave extraction, body wave extraction is a much greater challenge because ambient noise is typically dominated by surface wave energy. For each individual receiver pair, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
163
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(166 citation statements)
references
References 40 publications
(68 reference statements)
3
163
0
Order By: Relevance
“…Reconstructing HF body waves is of major interest because they have a sharp sensitivity to seismic velocity perturbations at seismogenic depths. Studies of Roux et al (), Nakata et al (), and Nakata et al () showed that, under specific virtual source and receiver configurations involving dense seismic arrays, it is possible to reconstruct body waves traveling in the shallow crust. These arrays are specifically designed for seismic interferometry so that the noise correlations between different pairs of sensors can be stacked along distance bins to increase the signal to noise ratio of the reconstructed Green's function.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstructing HF body waves is of major interest because they have a sharp sensitivity to seismic velocity perturbations at seismogenic depths. Studies of Roux et al (), Nakata et al (), and Nakata et al () showed that, under specific virtual source and receiver configurations involving dense seismic arrays, it is possible to reconstruct body waves traveling in the shallow crust. These arrays are specifically designed for seismic interferometry so that the noise correlations between different pairs of sensors can be stacked along distance bins to increase the signal to noise ratio of the reconstructed Green's function.…”
Section: Introductionmentioning
confidence: 99%
“…The cross correlations of ambient seismic noise have become indispensable in seismic tomography (e.g., Chen et al, ; de Ridder et al, ; Fang et al, ; Green et al, ; Lin et al, ; Mordret et al, ; Nakata et al, ; Nishida, Kawakatsu & Obara, ; Saygin & Kennett, ; Stehly et al, ; Yang et al, ; Zheng et al, ) and studies of attenuation and elastic (de) amplification (Bowden et al, ; Denolle et al, ; Harmon et al, ; Prieto et al, ). Current techniques are based on the assumption that cross correlations of the ambient seismic field converge to approximate interreceiver Green's functions (Boschi & Weemstra, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ambient noise correlation is capable of detecting surface (Campillo and Paul 2003;Shapiro and Campillo 2004), body (Roux et al 2005;Miyazawa et al 2008;Boué et al 2013;Nakata et al 2015), and reflected (Draganov et al 2007(Draganov et al , 2009Zhan et al 2010;Ryberg 2011;Poli et al 2012aPoli et al , 2012bRuigrok et al 2012;Tibuleac and von Seggern 2012) waves propagating within a background wavefield. Tonegawa et al (2013) calculated auto-correlation functions (ACFs) by using ambient noise at 1-3 Hz recorded by three broadband OBSs deployed on the outer rise region in the northwestern Pacific.…”
Section: Introductionmentioning
confidence: 99%